Estratégias de Produção in vitro de Bioinseticida Viral: influências do Isolado, da Cinética e do Modo de operação - Almeida, Andréa Farias de (2010)
Societal concerns about environmental sustainability has lead to the development of ecologically-friendly alternatives to chemical insecticides for crop protection. One such alternative is biological pest control. In particular, baculoviruses are well suited as insect biopesticides due to their narrow host specificity and relative ease of propagation. In Brazil, the baculovirus Anticarsia gemmatalis nucleopolyhedrovirus (AgMNPV) is the main biological control agent employed for the soybean pest, Anticarsia gemmatalis. This baculovirus biopesticide is currently produced using caterpillars, but increasing market demand for the product has encouraged the development of an in vitro manufacturing process, which can be scaled up to much higher virus productivities. In this study, three wild-type AgMNPV isolates (AgMNPV-2D, AgMNPV-MP2 and AgMNPV-MP5) and a recombinant form (vAgEGT-LacZ) were characterised in terms of occlusion body (OB) production and infection kinetics, to enable future optimisation of the in vitro production process. These viruses were propagated using a Spodoptera frugiperda (IPLB-SF21) insect cell line grown in shaker-flask batch cultures. Among the virus isolates tested, AgMNPV-MP5 was found to be the best producer, yielding (5.3±0.85)x108 OB/mL after 8 days post infection. The characterisation of vAgEGT-LacZ propagation in suspension cell cultures has not been previously reported in the literature; hence it became the main focus for this thesis. In particular, it was carried out a study on the effect of the multiplicity of infection (MOI) on OB production. Five successive batches were performed getting a final production (8.9±1.42)x1014 occlusion bodies, considering that production is related for a bioreactor with final volume of 10m3. A low MOI associated with a fed-batch process for vAgEGT-LacZ production was found to support a 3-fold higher OB yield when compared to the default batch process (1.8x107 and 5.3x107 OB/mL, respectively). This yield is competitive with regards to the production process.